Nutritional rickets: Still a problem for the pediatric population - BEREKET, ABDULLAH (My University, 2010)
Rickets is a mineralization disorder of the growing bone. Nutritional rickets is still prevalent in many parts of the developing world and is re-emerging in developed countries. Although vitamin D deficiency plays a central role in the pathogenesis of this disease, calcium deficiency and genetic factors may also cause or contribute to the development of rickets. This review will focus on the classical form of nutritional rickets, in other words, vitamin D-deficiency rickets. The epidemiology, ethiopathogenesis, risk factors, clinical picture, diagnosis, treatment and prevention of nutritional rickets are reviewed. © 2010 Future Medicine Ltd.
Keywords: Bone; Calcium; Cholecalciferol; Rickets; Vitamin D